MODIFICATION OF PALYNOFLORA IN THE MOSCOW SYNECLISE AT THE PERMIAN-TRIASSIC BOUNDARY - Yaroshenko O.P.; Lozovsky V.R. (My University, 1997)
Three microfloral assemblages are distinguished among palynomorphs occurring in Upper Permian (Vyatka Horizon) and Lower Triassic (Vokhma Horizon) terrestrial deposits of the Moscow syneclise. One of them, typical of the middle Vyatka Horizon (Luptyug Member), is distinct from another, confined to Lower Triassic beds of the Vokhma Horizon, whereas the third one, occurring in the upper Vyatka beds (Moloma Member), is transitional in composition. The data obtained suggest that a hiatus in sedimentation corresponding to the boundary epoch between the terminal Permian and earliest Triassic did not have identical time spans in different areas of the Moscow syneclise. According to the character of palynoflora and associated vertebrate fauna, it was minimal in the Vetluga River basin. The paper is supplemented with a description of the new pollen species Ephedripites permasensis Yaroshenko sp. nov. collected from the Krasnye Baki Subformation of the Vokhma Horizon.
Keywords: Triassic; Permian; Палеозой::Пермская; Paleozoic::Permian; Mesozoic::Triassic; Мезозой::Триасовая